Metastatic Primary Gastric Squamous Cell Carcinoma: An Uncommon Presentation of a Rare Malignancy - Michael Beattie; Ramy Mansour; Derek Thigpin; Carolyn Haus (Case Reports in Gastrointestinal Medicine)
Primary gastric squamous cell carcinoma is a very rare disease. A 53-year-old male with history of hypertension, alcoholism, and nicotine abuse presented to the hospital after a syncopal episode. He complained of bloating abdominal pain, early satiety, and poor appetite. A CT of his abdomen and pelvis revealed a gastric mass with diffuse hepatic metastasis. A gastric mass was seen on upper endoscopy and biopsies revealed gastric squamous cell carcinoma. There was no involvement of the esophagus. This case should add to the limited literature and serve as a reminder that while this is a rare malignancy, it must be considered when evaluating a gastric mass.